Pengaruh Bimbingan Klasikal Dengan Teknik Symbolic Modeling Untuk Meningkatkan Motivasi Belajar Siswa - Resnandhi Arhab Maramis (Prosiding University Research Colloquium, 2021)
This study aims to examine the effect of classical guidance with symbolicmodeling techniques to increase students' learning motivation. This research wasconducted to find the data needed to find out the increase in students' learning motivationat school, so this research is a very important step.This study uses an experimental research method, namely Pre-experimentaldesign, the research design used is a onegroup pretest-posttest design. The researchsample was taken by random sampling with a total of 24 students. Collecting data usingobservation, interviews and questionnaires. The instrument validity test was carried outby experts and tested statistically with the help of the SPSS 25.0 application program aswell as the reliability test. As for the data analysis technique using parametric statistics,namely the Wilcoxonsigned rank test with the SPSS 25.0 application program.The results showed that classical guidance with symbolic modeling techniqueshad an effect on increasing students' learning motivation. This is evidenced from theresults of the Wilcoxon test analysis by showing the value of Sig. of 0.001 and smaller thanthe 0.05 significance level. So it can be concluded that classical guidance with the use ofsymbolic modeling techniques can increase student learning motivation.